EXPLORING ENGLISH TEACHERS’ PERCEPTIONS ON USING SITUATIONAL LANGUAGE TEACHING METHOD IN TEACHING VOCABULARY - Yuliar Masna; Syarifah Dahliana; Nurul Aulia Martaputri (Getsempena English Education Journal, 2020)
The research was accomplished to investigate the perceptions of elemantary- school teachers on using Situational Language Teaching method in teaching vocabulary. The aims of this study were to examine the advantages of using situational language teaching method in teaching vocabularies and to investigate English teachers’challenges of using Situational Language Teaching method in teaching vocabulary. This research was completed by using a qualitative approach and the reseachers employed a semi-structured inteview to collect the data. The research participants were five English teachers who teach English subject at elementary schools in Aceh Barat. The results of this research indicate that the advantages of using this method were enhancing students’ motivation ,and creating an effective teaching-learning process. Then, the challenges of using Situational Language Teaching methods in teaching vocabulary were preparing course material and dealing with students’ boredom.